RELATIONSHIP OF ERGONOMICS, LIGHTING, AND NOISE WITH CHILDREN’S COMFORT AT TPA AL-MUNAWAR BUNGO - Tiara Nurcikita; Febri Mubin; Ayudhia Fasha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2026)
Learning environment is a crucial factor in supporting children's comfort and learning effectiveness, particularly in non-formal education settings such as Taman Pendidikan Al-Qur’an (TPA). Environmental components such as ergonomics, lighting, and noise may influence children’s physical and psychological conditions during learning activities. A quantitative cross-sectional design was conducted involving 30 children in TPA Al-Munawar Bungo, Indonesia, selected using total sampling. The independent variables were ergonomics, lighting, and noise, while children’s comfort was the dependent variable. Data were collected through direct observation of environmental conditions and a structured questionnaire assessing comfort. Descriptive statistics and bivariate analysis using Chi-Square and Fisher’s Exact tests were applied. The findings revealed a significant relationship between ergonomics and children’s comfort, while lighting showed a moderate association. Noise was not significantly related to comfort due to its relatively low and non-continuous intensity. Environmental factors, particularly ergonomics, play a vital role in determining children’s comfort in TPA settings; therefore, practical improvements and further studies with larger samples are recommended to strengthen environmental health policies in educational contexts.